The influence of compensation training development and career development on employee performance among non-academic permanent staff at Universiti Malaysia Sabah - Joehan Joehari William (2010)
This research investigates the influence of Compensation, Training development and career development on employee performance among non-academic permanent staff at Universiti Malaysia Sabah. This study only focuses on the three independent variable that were found to be the important benefits that are provided by human resource management in Universiti Malaysia Sabah to their permanent staffs. The mediating variable that is Job satisfaction been regarded as an individual's positive emotion reaction to improve performance for particular job and it also can be define as employee affective reaction to a job based on comparison between actual outcomes and desired outcome. Surveydoneon 118 non-academic permanent staff in the university discovered that only compensation in the independent variable factors were found to have significant relationship with employee performance, while the mediating variable that is Job satisfaction was proven to have relationship between independent variable(Compensation, Training and development, and career development) dependent variable (employee performance).The result of this study provides important insight to the management of the university pertaining to issue to improve the staff performance of the non-academic permanent staff.